Sistem Informasi Absensi di Kepolisian Sektor Bandar Pulau - Nur Saida (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
Attendance information system has an important role in improving the efficiency and accuracy of attendance recording in various institutions, including Bandar Pulau Police Station, which until now still uses manual methods. This research aims to develop a technology-based attendance information system to facilitate attendance data management, reduce recording errors, and speed up report generation. The research was conducted using qualitative method through observation, interview, and literature study. The results showed that the attendance system at Bandar Pulau Police Station was still done manually by recording in a book, which slowed down the data recording process. The research recommends a computer-based attendance information system to simplify the management of personal attendance data. The system design includes use case diagram and interface design, including login menu, attendance data input, and attendance report. The main objective is to develop a system that is more practical, efficient, and facilitates the attendance administration process within the police sector.